On the Efficiency of the Soil Digging Processes - Maciejewski, J.; Jarzębowski, A.; Trąmpczyński, W. (Engineering Transactions, 2001)
In the first part of the paper, an experimental verification of correctness of the common assumption that the plane strain conditions occur in the tests performed in soil bins is presented. An experimental program was executed basing on the soil cutting problem, with the application of vertical rigid walls of various widths as the working tools. It turned out that in the case of the tool width equal to the width of the soil bin, the soil cutting problems may be treated as the plane strain processes. The influence of the friction phenomena on the side walls of the bin was estimated. For the tools for which no interaction with the side walls of the bin was observed, the zone of the plane strain deformation occurred in the central part of the tools. Then the characteristic deformation patterns and force-displacement relations for the L-shaped tool are determined. Finally, the new idea of the optimization of digging be means of the earth-working machinery is presented and experimentally verified. Dividing the whole excavation task into several repeatable cycles for which the soil free boundary before and after the experiment are similar, the optimization of the single cycle plays a significant role in the energetic efficiency of the whole task. The single cycle of the working process is defined using several basic parameters. The influence of each parameter on the specific unit energy of the process is experimentally verified. The set of values of the discussed parameters is recommended for the particular soil and tool shape. The disadvantages of other soil cutting strategies are discussed.